IET International Conference on Wireless Communications and Applications (ICWCA 2012) 2012
DOI: 10.1049/cp.2012.2109
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Power Control in Mobile Wireless Sensor Networks: Simulation-based Approach

Abstract: Saving energy is a very critical issue in wireless sensor networks (WSNs) because sensor nodes have a severe resource constraints such as lack of processing power and limited in power supply. Since the communication is the most energy consuming activities in WSNs, the power use for transmission or reception of packet should be managed properly. Transmission power control (TPC) technique is one of the techniques to reduce energy consumption which has been widely studied in mobile ad-hoc networks (MANETs). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…TPC sets the radio transmission power of each node to an appropriate level according to the communication distance, which enables preventing the networks from having an isolated node which does not have a path to reach the sink. In [14], TPC mechanism is implemented in the adhoc on-demand distance vector (AODV) routing protocol for mobile WSNs, and it is shown that implementation of TPC has some positive impact on networks in respect to energy consumption. In [15], the minimum spanning tree rooted at one source node is constructed on the basis of TPC, and it is clarified that compared to the disk model, the variable-range strategy can save transmission power, as well as improving the traffic capacity.…”
Section: Algorithm 1 Pnf Routingmentioning
confidence: 99%
“…TPC sets the radio transmission power of each node to an appropriate level according to the communication distance, which enables preventing the networks from having an isolated node which does not have a path to reach the sink. In [14], TPC mechanism is implemented in the adhoc on-demand distance vector (AODV) routing protocol for mobile WSNs, and it is shown that implementation of TPC has some positive impact on networks in respect to energy consumption. In [15], the minimum spanning tree rooted at one source node is constructed on the basis of TPC, and it is clarified that compared to the disk model, the variable-range strategy can save transmission power, as well as improving the traffic capacity.…”
Section: Algorithm 1 Pnf Routingmentioning
confidence: 99%
“…Therefore, a particular application may make use of the network data over the internet, using a PDA, or even a desktop computer [15].…”
Section: End Usermentioning
confidence: 99%
“…TPC sets the radio transmission power of each node to the right level according to the communication distance, which enables preventing the networks from the dead-end problem. In [3], TPC mechanism is implemented in AODV routing protocol for mobile WSNs, and it is shown that the implementation of TPC has some impact on the networks in respect to energy consumption. In [4], the minimum spanning tree rooted at one source node is constructed on the basis of TPC, and it is clarified that compared to the disk model, the variable-range strategy can save transmission power, as well as improving the traffic capacity.…”
Section: Introductionmentioning
confidence: 99%